Computed tomography-based characterization of impact and fatigue after impact behavior of carbon fiber-reinforced polyurethane. (1st June 2022) - Gerdes, Lars; Richle, Stefan; Mrzljak, Selim; Hülsbusch, Daniel; Barandun, Gion; Walther, Frank
Abstract: With the increasing use of fiber-reinforced polymers in safety–critical applications, detailed investigations of material behavior under various mechanical loads are mandatory. Since carbon fiber-reinforced polyurethane can often be found in aerospace and automotive industries, good impact resistance is required for potential crashes and bird strikes. Besides the determination of characteristic values from impact and cyclic tests, the impact damage detection and observation in subsequent tests via non-destructive testing, is of prime importance. Thus, the impact resistance of CFR–PU was investigated with subsequent comparison of different methods for damage detection. The fatigue after impact performance was carried out by performing multiple amplitude tests. The impact tests resulted in a linear grow of damage area with increasing impact energies. Multiple amplitude tests showed a significant decrease in fatigue after impact strength, especially, if fiber failure and delamination occurred. The successive material damage could be described by evaluating dynamic stiffness and specimen temperature.